STRATEGI PENINGKATAN INDEKS PERTANAMAN PADI SAWAH DI KABUPATEN LEBONG - Dinata, Kusmea; Hidayat, Taufik; Yartiwi, Yartiwi; Yuliasari, Shannora; Musaddad, Darkam; Sastro, Yudi (Jurnal AGRISEP, 2021)
Lebong including rice-producing areas, but this commodity is mostly newly cultivated one plant in one year. The purpose of this study was to develop a strategy for increasing the rice cropping index (CI) in Lebong Regency. This research was conducted in the month of January 2019 s / d February 2019 by the method of FGD and interviews with the Department of Agriculture, extension workers, farmers, village heads and Babinsa . The activities of research to identify the internal factors (strengths and weaknesses) and external factors (opportunities and threats) being done with SWOT analysis method. Research results obtained factor major internal and external power factor in the form of program/policy of local government in improving the CI rice in Lebong, a factor of weakness is capacity extension of the weak, chance factor is technological innovation to increase the productivity of rice plants and factors threaten is culture farmers which believe that rat pests cannot be controlled. The strategy formulation is done by utilizing the power factor to avoid threats with maximize the performance of extension workers and village through instruction Regent, and make technological innovation pilot rice cultivation on a large scale in an overlay.